Staying, leaving and returning: Trends of prevention of mother-to-child transmission retention among newly diagnosed HIV-positive pregnant and postpartum women. (January 2022) - Abraham, Susanna A; Clow, Sheila E
Uptake of services and retention throughout the Prevention of Mother-to-Child Transmission continuum are necessary to achieve the goal of reducing Mother-to-Child Transmission of Human Immunodeficiency Virus (HIV). Adopting a retrospective cohort design, we tracked the uptake of services in a district hospital in Ghana from antenatal booking through to six weeks postnatal when early infant diagnosis was conducted. Of the 1252 pregnant women booked antenatally, 94.1% ( n = 1178) received pre-test counselling, 96.3% (1134) opted for HIV testing and 3.8% ( n = 43) women tested positive for HIV throughout the continuum. The retention rate at six weeks postpartum was 67.4%. Missed opportunities occurred throughout the programme and the highest disengagement, 58.9% (23/39) occurred antenatally. Instances of re-engagement were also recorded. Establishing measures to promote retention throughout the programme is critical to ensuring HIV-infected mothers maintain their health and their exposed newborns are HIV-free. This phase of the study provided a comprehensive view of retention in the absence of any baseline.